Implementasi KMA 183 Dalam Kurikulum Bahasa Arab Di Madrasah Aliyah Al Amiriyyah Berbasis Pesantren Blokagung Banyuwangi - Kholiq, Ilham Nur; Insaniyah, Anyes Lathifatul (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
Learning Arabic at Madrasah Aliyah has so far emphasized mastery of maharah, namely maharah istima', kalam, qir?'ah and kit?bah. This aims to encourage, guide, develop and nurture abilities as well as foster a positive attitude towards the Arabic language, both receptive and productive. Receptive ability is the ability to understand other people's speech and comprehend reading. The aim of this research is to describe the implementation of the 2019 KMA 183 Arabic language curriculum. And the research method used in this research is descriptive qualitative, by extracting data using observation, interviews and documentation, while the analysis uses data reduction, data presentation and drawing conclusions. The results of the research are (1) The curriculum used at Madrasah Aliyah Amiriyyah in Arabic subjects for the 2022/2023 academic year is the KMA 2019 curriculum which is oriented towards character education with reference to KI 1 and KI 2. As for character education at Madrasah Aliyah al Amiriyyah Blokagung Banyuwangi has three aspects, such as religiosity, monotheism, concern and nationalism. These three aspects are formed during the process of learning Arabic in class. (2) The supporting factor for learning Arabic at Madrasah Aliyah Al Amiriyyah is the large number of educational units and language institutions that use the madrasa as a place for research and collaborate with madrasas. And the inhibiting factor is that students think that Arabic is not an important material in madrasas. Students also feel bored because they often study Arabic at Islamic boarding schools every day. Apart from that, the obstacles felt by teachers are the limited time given and the lack of freedom in using developing Arabic language learning technology.